Effect of Feeding Frequency on Finisher Phase Broiler Performance and Production - Soraya Faradila; N Nuraeni; Aryanto Ghuta; Fajar Al’fiqram (JURNAL GALUNG TROPIKA, 2022)
This study aims to determine the effect of the feeding frequency on the performance and production of finisher phase broilers. The study used a completely randomized design (CRD) with 4 treatments and 4 replications. Each cage consisted of 5 chickens, so 80 chickens aged 22 days were used and maintained for 2 weeks. Treatments included giving once (at 17.00), twice (at 07.00 and 19.00), three times (at 07.00, 15.00, and 23.00), and four times (at 05.00, 11.00, 17.00, 23.00). Parameters measured were consumption performance, weight gain, feed conversion, and broiler production which consisted of carcass percentage and abdominal fat. The results showed that the feeding frequency on broiler performance and production had no significant effect (P> 0.05). Feeding once is the best treatment with efficiency based on time and effort.